Bimbingan Karir Anak Berbasis Kearifan Lokal Bugis - Adnan Achiruddin Saleh (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Local wisdom of Bugis is the value of goodness which is agreed upon and carriedout for the Bugis community, known as pappaseng. One of the pappaseng in the scope ofchildcare is the palettu alenu riolo tejjokanu, it is important to be conveyed openly withthe consideration that it becomes knowledge and application for children themselves andothers and also discussion discourse for academics in testing scientific principles andopportunities in scientific integration. This pappaseng can openly become material incareer guidance for both parents and professionals engaged in childcare. Theimplementation of the child's career guidance can be in the initial stages in mapping thechild's abilities and compatibility with the job. Palettu alenu riolo tejjokanu can beapplied to children’s career guidance through children’’s career imaginations, careerplays, chindren’s chech list behavior, and children’s open discussions.